Competitive Inhibitors Unveil Structure/Function Relationships in Human D-Amino Acid Oxidase - Molla, Gianluca (Frontiers in Molecular Biosciences, 2017)
D-amino acid oxidase (DAAO) catalyzes the oxidative deamination of several neutral D-amino acids and is the enzyme mainly responsible (together with serine racemase) for degrading D-serine (D-Ser) in the central nervous system of mammals. This D-amino acid, which binds the coagonist site of the N-methyl-D-aspartate receptor, is thus a key neuromodulator of glutamatergic neurotransmission. Altered D-Ser metabolism results in several pathological conditions (e.g., amylotrophic lateral sclerosis or schizophrenia, SZ) for which effective “broad spectrum” pharmaceutical drugs are not yet available. In particular, the correlation between reduced D-Ser concentration and SZ led to a renaissance of biochemical interest in human DAAO (hDAAO). In the last ten years, public and corporate research laboratories undertook huge efforts to study the structural, enzymatic, and physiological properties of the human flavoenzyme and to identify novel effective inhibitors which, acting as pharmaceutical drugs, could decrease hDAAO activity, thus restoring the physiological concentration of D-Ser. Although none of the identified hDAAO inhibitors has reached the market yet, from a biochemical point of view, these compounds turned out to be invaluable for gaining a detailed understanding of the structure/function relationships at the molecular level in the mammalian DAAO, in particular of the interaction between ligand and the enzyme. This detailed knowledge, together with several recent studies concerning the interaction of the human enzyme with other protein regulative partners, its subcellular localization, and in vivo degradation, contributed to gaining comprehensive knowledge of the structure, function, and physiopathological role of this important human enzyme.